Peculiarities of Civil Actions in Criminal Procedure - Ivan Vernydubov; Svitlana Belikova (Наукові записки НаУКМА: Юридичні науки, 2019)
According to the amendments to the Civil Procedure Code of Ukraine (GIC of Ukraine) introduced on December 15, 2017, the updated procedure for the consideration of a civil claim in court is actually updated, which cannot but affect the legal norms of the Criminal Procedure Code of Ukraine (CPC of Ukraine). At the same time, the adopted legislative changes contribute to bringing some provisions of the Code of Criminal Procedure of Ukraine in line with the legal norms of the Code of Civil Procedure of Ukraine. This will avoid legal problematic issues the judicial review of a civil lawsuit in a criminal proceeding. The feature of civil lawsuit in criminal proceedings is emphasized. The purpose of the article is, on the basis of the analysis of the current procedural legislation, to highlight the issue of bringing a civil action in criminal proceedings and its trial with the provision of proposals for amendments to the Criminal Procedure Code of Ukraine in this area. According to Part 5 of Article 128 of the Code of Criminal Procedure of Ukraine, a civil claim in criminal proceedings is considered by the court according to the rules established by this Code. If the procedural relations arising in connection with a civil suit are not regulated by this Code, the norms of the Civil Procedure Code of Ukraine shall apply to them, provided that they do not contradict the principles of criminal proceedings. However, today a number of legal provisions regarding the judicial review of a civil claim in criminal proceedings are not regulated by the Criminal Procedure Code of Ukraine. Conversely, the new provisions of the Code of Civil Procedure of Ukraine, regulating the procedure for resolving civil disputes, may be contradictory or incomprehensible given the existing Criminal Procedure Code of Ukraine. As a result of such legal gaps, difficulties may arise in exercising their representative powers in criminal proceedings. According to the results of the study, the authors consider it expedient to bring the legal norms of the Criminal Procedure Code of Ukraine (Articles 128, 315, 316) into conformity with regard to the court proceedings of a civil claim to the norms of the Code of Civil Procedure of Ukraine.